(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Every employee who has been working at the company should ideally receive a refresher on the material they have previously learned in college. The refresher material provided is related to the tasks and responsibilities of employees’ work in the company. Then the purpose of implementing this PkM is to enhance the capacity and capability of the company’s employees, which will ultimately support the skills needed to carry out tasks and responsibilities in the company. One of the Tri Dharma of Higher Education is to carry out Community Service (PkM). In this PkM activity, the PkM Team from Trisakti School of Management provided a refresher on the material at PT. AAM. PT. AAM is a pharmaceutical distribution company. The refresher material consists of 3 (three) sub-modules of the Accounting Information System, namely Revenue Cycle, Expenditure Cycle, and General Ledger and Reporting System. To achieve the PkM objectives, the material will be delivered through workshops. The method used in this PkM activity is through tutorials and discussions. Next, after the PkM activities were carried out, an evaluation activity was conducted for the employees. The evaluation results show good scores, with 88 for revenue cycle, 80 for expenditure cycle, and 69 for general ledger and reporting system. The limitation in this PkM activity is the issue of time. Because the participants, who are employees at the company, have tasks and responsibilities that must be completed. The suggestion for the next PkM activity is to use Case Studies. With case studies, it is hoped that the employees will also gain a more comprehensive understanding of the Accounting Information System material. — Setiap karyawan yang sudah bekerja di perusahaan, ada baiknya untuk mendapat penyegaran kembali atas materi yang sudah pernah diperoleh di bangku kuliah. Materi penyegaran yang diberikan adalah yang terkait dengan tugas dan tanggung-jawab atas pekerjaan karyawan di perusahaan. Kemudian tujuan pelaksanaan PkM ini adalah untuk meningkatkan kapasitas dan kemampuan karyawan perusahaan yang pada akhirnya akan mendukung ketrampilan untuk melaksanakan tugas dan tanggung-jawab di perusahaan. Salah satu Tri Dharma Perguruan Tinggi adalah melaksanakan Pengabdian kepada Masyarakat (PkM). Pada kegiatan PkM ini Tim PkM dari Trisakti School of Management memberikan penyegaran materi di PT. AAM. PT. AAM merupakan perusahaan distributor farmasi. Materi penyegaran adalah 3 (tiga) sub-modul dari Sistem Informasi Akuntansi, yaitu Revenue Cycle, Expenditure Cycle, dan General Ledger and Reporting System. Untuk mencapai tujuan PkM, penyampaian materi dengan cara lokakarya (workshop). Metode yang digunakan dalam kegiatan PkM ini adalah dengan tutorial, diskusi. Selanjutnya setelah kegiatan PkM dilaksanakan, dilakukan kegiatan evaluasi terhadap para karyawan. Hasil evaluasi menunjukkan nilai yang baik dengan hasil 88 untuk revenue cycle, 80 untuk expenditure cycle, dan 69 untuk general ledger and reporting system. Keterbatasan dalam kegiatan PkM ini adalah masalah waktu. Karena para peserta yang sebagai karyawan di perusahaan, mempunyai tugas dan tanggung-jawab yang harus diselesaikan. Saran untuk kegiatan PkM berikutnya adalah dengan menggunakan Studi Kasus. Dengan studi kasus, diharapkan para karyawan juga memperoleh pemahaman lebih menyeluruh mengenai materi Sistem Informasi Akuntansi.